2018
DOI: 10.3389/fimmu.2018.02707
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Stress Surveillance Response Contributes to Vitiligo Pathogenesis

Abstract: Vitiligo is a chronic multifactorial depigmentation disorder characterized by the destruction and functional loss of melanocytes. Although a direct cytotoxic T cell attack is thought to be responsible for melanocyte damage, the events leading to the loss of self-tolerance toward melanocytic antigens are not understood. This research aimed to identify novel cellular and molecular factors that participate in vitiligo pathogenesis through the application of gene expression and immunofluorescence analysis of skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
0
17
1
Order By: Relevance
“…Damaged cells upregulate stress ligands and IFN production. IFNs induce CXCL10 secretion from keratinocytes, which then attracts CXCR3-positive T cells [ 25 ]. Besides, TNF- α , IL-1 β , and IFN- γ can induce another cytotoxic effector molecule, inducible nitric oxide synthase (iNOS) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damaged cells upregulate stress ligands and IFN production. IFNs induce CXCL10 secretion from keratinocytes, which then attracts CXCR3-positive T cells [ 25 ]. Besides, TNF- α , IL-1 β , and IFN- γ can induce another cytotoxic effector molecule, inducible nitric oxide synthase (iNOS) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The glutamate/cysteine antiporter (System Xc‐) deficiency has also been claimed to cause cell death through activating ER stress and autophagic process in MCs (Zheng et al., 2016). Moreover, one study reported that keratinocytes and the scarce remaining MCs in vitiligo lesions had significantly more autophagic vacuoles, in comparison with control and non‐lesional skin (Raam et al., 2018). However, although autophagic process is frequently induced in a vast number of pathophysiologic settings, autophagic cell death rather than cell death with autophagy is another condition (Kroemer & Levine, 2008).…”
Section: Conventional Forms Of Cell Death In Vitiligomentioning
confidence: 99%
“…In melanocytes, upregulation of stress‐related MICA/MICB expression will activate innate immune cells (Raam et al., 2018), and increasing numbers of IFN‐γ–secreting LC1 and NK cells are found in blood and non‐lesional vitiligo skin (Tulic et al., 2019). Involvement of heat‐shock proteins is also indicated by demethylation of the HIF1α promoter in vitiligo CD8+ T cells (Deng et al., 2019).…”
Section: Marking T‐cell Activationmentioning
confidence: 99%
“…Involvement of heat‐shock proteins is also indicated by demethylation of the HIF1α promoter in vitiligo CD8+ T cells (Deng et al., 2019). The latter can show prominent expression of EOMES, accompanied by “virtual” innate memory cell development (Raam et al., 2018). Interestingly, we found increased EOMES:Tbet expression in response to modified HSP70i (Mosenson et al., 2013).…”
Section: Marking T‐cell Activationmentioning
confidence: 99%